Negative representations of young people in local comic books / Roselina Musahar, Nurus Syahidah Tahreb and Norsuraya Mohd Noor - Musahar, Roselina; Tahreb, Nurus Syahidah; Mohd Noor, Norsuraya (Universiti Teknologi MARA Cawangan Pahang, 2013)
The presence of the many comic books in today’s local media scenario cannot be disputed. As such, comic books do not only serve as a form of entertainment but may be a powerful source of influence to the readers especially the young ones. Being young and immature may cause problems to these young ones where whatever they read is observed to be true and have impacts on their behaviour and attitudes in real life. Whether young people are being represented in acceptable and desirable ways can be an interesting phenomenon to observe. Thus, this paper discusses the representations of young people as portrayed by the comic book artist in several issues of one of the comic books available in the local market. This study used content analysis method to analyse the comic book strips for the depiction of youngsters by focusing on their attitudes and behaviour. Findings indicate that young people are represented in several different ways that can be influential to the minds of the young ones and the perception of others about them.